Study on Environmental Causes and SNPs of MTHFR, MS and CBS Genes Related to Congenital Heart Disease. - Hui Shi (PLoS ONE, 2015)
Congenital heart diseases (CHD) are among the most common birth defects in China. Environmental causes and folate metabolism changes may alter susceptibility to CHD. The aim of this study is to evaluate the relevant risk-factors of children with CHD and their mothers.138 children with CHD and 207 normal children for controls were recruited. Their mothers were also enlisted in this study and interviewed following a questionnaire about their pregnant history and early pregnancy situation. Five single nucleotide polymorphisms (SNPs) in methylenetetrahydrofolate reductase (MTHFR), methionine synthase (MS) and cystathionine β-synthase (CBS) of mothers and children were genotyped.There were significant differences in the gender of children, occupation of mothers, family history with CHD, history of abortion, history of adverse pregnancy, early pregnancy health, fetus during pregnancy, pesticide exposure and drug exposure in CHD group and control group ( P < 0.05). Logistic regression analyses showed that after adjustment for above factors, MTHFR rs1801131 were significantly associated with their offspring CHD risk in mothers. Compared with the mothers whose MTHFR were rs1801131 AA and AC genotypes, the mothers who got a mutation of MTHFR rs1801131 CC genotypes had a 267% increase in risk of given birth of a CHD children (OR = 3.67,95%CI = 1.12-12.05). Meanwhile, MTHFR rs1801131 were significantly associated with CHD susceptibility in children (OR = 1.42, 95% CI = 1.00-2.44 in additive model).Besides mothers' social and fertility characteristics, our results suggested that the genetic variants in folate metabolism pathway might be one of the most related risk-factors of CHD. MTHFR rs1801131 were identified as loci in Chinese population that were involved in CHD.